Performing trust: Social media, reputational labor, and economic legitimacy in Indonesia's informal errand economy - Lia Hilyatul Masrifah (Digital Theory, Culture & Society, 2026)
This study examines how informal errand service providers (jasa suruh) in Indonesia construct and sustain economic legitimacy on social media in the absence of institutional support and formal regulation. It conceptualizes this condition as a digital gray space, where legitimacy is generated through collective social verification rather than institutional recognition. Drawing on Roy’s gray space concept (2005), Pierre Bourdieu’s social capital theory (1986), and Aihwa Ong’s porous sovereignty framework (2006), this study observed seven jasa suruh accounts across Instagram, WhatsApp, and personal websites, and conducted in-depth interviews with 20 participants, comprising nine providers and eleven users in urban Java. Three main findings emerged. First, digital visibility simultaneously facilitates trust formation and market access while increasing reputational risk. Second, social capital functions both as an entry mechanism into the informal economy and as a disciplinary force that intensifies the reputational vulnerability of workers lacking institutional protection. Third, the absence of formal governance shifts transactional and reputational risks onto individual workers and users, thereby reproducing structural precarity. This study contributes to digital communication sociology, informal labor studies, and urban informality by demonstrating that social media functions as a performative infrastructure of legitimacy that is communicatively constructed, institutionally unprotected, and inherently fragile.